2017
DOI: 10.4314/ijbcs.v10i5.23
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical studies on the effect of diclofenac sodium on Wistar <i>Rattus norvegicus</i>

Abstract: Diclofenac sodium is a non-steroidal anti-inflammatory drug commonly used worldwide for the treatment of inflammation and pain due to arthritis or other ailments in man and animals. Despite these benefits, there are concerns that this drug may have adverse effect on animal's liver and kidneys. This work was designed to determine the effect of diclofenac sodium on blood components using haematological tests, as well as determine the hepatotoxic and nephrotoxic effects using biochemical assays. Twenty rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
5
19
0
1
Order By: Relevance
“…These results are highly correlated with Basvaraj et al (Thanagari et al, 2012), Nasir AS et al andZeyneb HK et al (El-Maddawy andEl-Ashmawy, 2013). Bilirubin is the excretory product from the catabolism of heme, which is normally conjugated by the liver and excreted through bile, increased serum bilirubin is an indicator of liver impairment our results are also correlated with Orinya Agbaji et al (Orinya et al, 2017). It has been reported that increase in the total bilirubin level is an indication of either excessive production of bilirubin in hemolytic anemia, potential damage by chemical toxins, decreased hepatocellular excretion and impaired intrahepatic and extrahepatic bile low (Lee, 1995).…”
Section: Discussionsupporting
confidence: 77%
“…These results are highly correlated with Basvaraj et al (Thanagari et al, 2012), Nasir AS et al andZeyneb HK et al (El-Maddawy andEl-Ashmawy, 2013). Bilirubin is the excretory product from the catabolism of heme, which is normally conjugated by the liver and excreted through bile, increased serum bilirubin is an indicator of liver impairment our results are also correlated with Orinya Agbaji et al (Orinya et al, 2017). It has been reported that increase in the total bilirubin level is an indication of either excessive production of bilirubin in hemolytic anemia, potential damage by chemical toxins, decreased hepatocellular excretion and impaired intrahepatic and extrahepatic bile low (Lee, 1995).…”
Section: Discussionsupporting
confidence: 77%
“…Creatinine and urea levels are used as markers of kidney function due to chemical stresses, but the test for creatinine is more sensitive than urea (Vasudevan & Sreekumari, 2007;Orinya, Adenkola, & Ogbe, 2016). The results obtained herein revealed that, Diclo, Ibu, and Para administration for 1 month had no significant alternations in renal function (levels of urea and creatinine).…”
Section: Discussionmentioning
confidence: 62%
“…This observation is also in agreement with the earlier reports on paracetamol of Oyedeji et al (2013) and Hossain et al (2003). Likewise, Orinya et al (2016) reported that after administrating diclofenac decreased Hb content in wistar rats. Similar results have been observed in dogs following diazepam administration by Suresha et al (2012).…”
Section: Hemoglobin Content (Hb Gm %)mentioning
confidence: 91%
“…Paracetamol is a widely used analgesic and antipyretic drugs (Anderson et al, 1998;Vane et al, 1998). Diclofenac sodium is a widely circulated drug, used both in humans and animals for the treatment and management of inflammation, fever and pain associated with disease or injury of domestic livestock and humans (Orinya et al, 2016). Pantoprazole are the drug whose main action is pronounced and long-lasting reduction of gastric acid production (Bigoniya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%